Repeated sudden sensorineural hearing loss with intralabyrinthine hemorrhage in a patient with Glanzmann thrombasthenia: case report - Tsuzuki, Nobuyoshi; Wasano, Koichiro; Ozawa, Hiroyuki (Frontiers in Audiology and Otology, 2024)
Glanzmann thrombasthenia is a rare congenital bleeding disorder. Recent advances in magnetic resonance imaging (MRI) have made it possible to detect micro-lesions in the inner ear, such as intralabyrinthine hemorrhage, a rare disorder that causes sudden hearing loss or vertigo. We present a case of 62-year-old female with Glanzmann thrombasthenia. Over a 10-year period, the patient had experienced seven episodes of left-sided sudden hearing loss (SHL). Although each episode was treated with steroids, her left-ear hearing level gradually worsened. Head T1-weighted MRI performed 27 days after onset of the sixth SHL episode showed hyperintense lesions throughout the left inner ear. The patient was diagnosed with intralabyrinthine hemorrhage. When a patient with hematologic disease or who is on anticoagulant therapy presents with SHL or vertigo, T1-weighted MRI should be performed within 1 month of symptom onset to confirm intralabyrinthine hemorrhage.